"How many miles make an inch?" Center-state relations and the 1967 India-Burma boundary agreement. Issue 5 (20th October 2019) - Paliwal, Avinash
ABSTRACT: Unabated protests in Manipur against India's boundary with Myanmar and the lack of demarcation of some boundary pillars, despite the signing of the India-Burma Boundary Agreement in 1967, makes it an important case to study how center-state relations impact India's foreign policy decision-making and implementation processes. Based on fresh archival material, this article explains why New Delhi refused to consult state governments in Northeast India before signing the boundary agreement, and the limiting consequences of such a top-down decision-making approach during the demarcation phase. A postcolonial entity that struggled to generate legitimacy in and assert sovereign control over the Northeast, India's approach on this issue offers an opportunity to reflect upon the (limited) conceptualization of, and ongoing debates around, the idea of a 'state' within foreign policy analysis.